PENERAPAN MODEL PEMBELAJARAN THE POWER OF TWO DALAM MENINGKATKAN HASIL BELAJAR SISWA DI SMP NEGERI 4 ALASA - Jaya Zalukhu, Tober Putra; Harefa, Yearning; Zebua, Serniati; Lase, Asali (Jurnal Tunas Pendidikan, 2023)
The application of The Power of two Learning Model is one of the learning models that uses cooperation between students in groups to achieve learning goals and students are divided into small groups and directed to study the subject matter that has been determined. Based on the results of teacher observations in Cycle I, the percentage of observations was 65.8 and in Cycle II it increased to 85.83%. The results of observations of student activity in Cycle I with the percentage of observation of student activity is 48.87% and in Cycle II increased to 88.82%, student learning achievement in Cycle I average value reached 64.9, and the percentage of learning completeness = 22.72%, and in Cycle II the average value increased to 78.80 with learning completeness = 81.81%. Thus it is concluded that increased student activity and learning outcomes in the Integrated Social Studies learning process, and the application of the power of two learning model can be applied to Integrated Social Studies subjects.